ECT in the time of the COVID-19 pandemic. (October 2020) - Ramakrishnan, Venkata Subramanian; Kim, Young Kwang; Yung, Wanda; Mayur, Prashanth
Objective: The recent and ongoing COVID-19 pandemic outbreak has placed a huge burden on healthcare systems worldwide. This emergent situation applies invariably to mental health services, and policy makers have issued new directives to adequately deal with this crisis. The COVID-19 outbreak poses special challenges to the administration of electroconvulsive therapy (ECT) since the anaesthetic induction is an aerosol-generating process. The report provides a narrative account of modifications to the ECT practice at a tertiary care psychiatric hospital to mitigate the risk of COVID-19 transmission. Conclusion: We emphasise two main modifications: use of personal protective equipment (PPE) during the ECT and modifications in the anaesthetic procedure to mitigate potential transmission.